2018
DOI: 10.1111/jce.13484
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in safety and complication rates of catheter ablation for atrial fibrillation

Abstract: The safety profile of AF ablation has improved significantly in less than a decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 16 publications
1
56
2
2
Order By: Relevance
“…A recent study on catheter ablation in AF patients suggested increasing proportion of patients with OSA undergoing catheter ablation for AF in the modern era cohort (2014‐2015) when compared with historic cohort (2009‐2011). These findings suggest that these coexistences remain an ongoing issue in the modern era …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A recent study on catheter ablation in AF patients suggested increasing proportion of patients with OSA undergoing catheter ablation for AF in the modern era cohort (2014‐2015) when compared with historic cohort (2009‐2011). These findings suggest that these coexistences remain an ongoing issue in the modern era …”
Section: Introductionmentioning
confidence: 82%
“…These findings suggest that these coexistences remain an ongoing issue in the modern era. 14 Continuous positive airway pressure (CPAP) is a well-known, effective therapy for OSA. Several studies have demonstrated favorable effects of CPAP therapy on preventing arrhythmias recurrence, heart rate control in patients with AF, and in decreasing severity and/or frequency of ventricular extrasystoles 3,7,13,15 Although the exact mechanism of CPAP use improves the success of AF treatment remains unclear, it has been suggested to be due to a reduction of the structural and electrical remodeling of the left atrium and oxidative stress, resulting in a lower recurrence rate of AF.…”
Section: Introductionmentioning
confidence: 99%
“…The only complication observed among day‐cases was a right phrenic nerve palsy in a cryoballoon ablation: this well‐known risk is usually a transient phenomenon and indeed it had resolved on patient return to the ward, allowing same‐day discharge as planned. As an expectation of a low complication rate is critical while planning for wide adoption of a day‐case ablation strategy, it is notable that a decrease in AF ablation complication rates overall has been observed lately . This is particularly the case with the increasing use of ultrasound for vascular access, as vascular complications are by far the most common and those most likely to preclude early mobilization and same‐day discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tamponade is a common, potentially life‐threatening complication during radiofrequency ablation of atrial fibrillation (RAAF) and must be addressed in a timely manner 1–3 . Pericardiocentesis is used to relieve the tamponade in the vast majority of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac tamponade is a common, potentially life-threatening complication during radiofrequency ablation of atrial fibrillation (RAAF) and must be addressed in a timely manner. [1][2][3] Pericardiocentesis is used to relieve the tamponade in the vast majority of patients. If patients show hemodynamic stability and no sign of pericardial bleeding, the pericardial drain can be removed.…”
Section: Introductionmentioning
confidence: 99%